Pemetaan Batimetri dan Analisis Pasang Surut untuk Menentukan Elevasi Lantai dan Panjang Dermaga 136 di Muara Sungai Mahakam, Sanga-Sanga, Kalimantan Timur - Purwanto, Adiguna Rahmat Nugrahav, Siddhi Saputro, (Jurnal Semesta Teknika, 2013)
Mahakam River estuary water located in East Kalimantan is territorial water that often traversed by ships transporting coal and passengers. A dock is needed in order to support such transportation activities. Sanga-Sanga Unit of Pertamina was planning to rebuild the dock that has been existed since the 1980s in the waters of the Mahakam River estuary, thus bathymetry mapping and tidal behavior analysis are needed. Bathymetry mapping and tidal behavior analysis are two important parameters in determining the elevation of the dock floor. The purpose of this study is to obtain information on the bathymetry condition and the tidal behavior that will be used as reference of boundary conditions in determining floor elevation and dock length of the Mahakam River estuary water. Field data collection was conducted on 18 to 21 September 2012 in the water Mahakam River estuary, Sanga - Sanga, East Kalimantan. The method being used is a quantitative method, and analysis using statistical or model. Mahakam River estuary waters depth was found being between -1,3 to - 8,6 meters. It was mixed with tidal type with prominent double type, where MSL 82 cm to 260 cm interval tides, MLWL (- 28,60 cm), LLWL (- 90 cm) and HHWL (+167 cm). Dock floor elevation was obtained being +2.76 m with a value of Zo as a point of ± 0,00 m and + 2,04 with MSL as a point of ± 0,00 m, while the length of the dock is recommended to serve one boat with Loa 95,70 m is 114,84 m. With the water depth in front of the dock is needed to serve the largest ships draft is - 5 m in order to dock the ship safely.